Role of Cytochrome P450 Enzymes in Pediatric Drug Metabolism: Physiological and Biochemical Perspectives; Systematic Review: Role of Cytochrome P450 Enzymes in Pediatric Drug Metabolism - Kalsoom, Rizwana; Sarwar, Zarka; Khan, Mehreen Nawaz; Hakim, Farzan; Shah, Furqan Ali; Fida, Najma (Pakistan Journal of Health Sciences, 2026)
Cytochrome P450 (CYP450) enzymes are central to pediatric drug metabolism. However, enzyme maturation (ontogeny) and pharmacogenetic variability produce substantial age-dependent differences in drug clearance, exposure, and toxicity risk across neonatal, infant, and childhood populations. Objectives: To synthesize contemporary evidence (2020–2025) on CYP450 ontogeny and pharmacogenetic variability in children and evaluate their clinical implications for drug clearance, dosing optimization, and safety. Methods: A systematic review was conducted according to PRISMA 2020 guidelines. PubMed, Scopus, Web of Science, and Google Scholar were searched for pediatric studies evaluating CYP450 ontogeny, pharmacokinetics, or pharmacogenetics. Eligible designs included observational studies, physiologically based pharmacokinetic (PBPK)/population PK modeling, real-world analyses, and systematic reviews. Risk of bias was assessed using the Newcastle–Ottawa Scale and AMSTAR. Due to heterogeneity, findings were synthesized narratively. Results: Sixteen studies from Asia, Europe, North America, and Australia were included. CYP2C19, CYP3A4, and CYP2D6 were the most frequently investigated isoforms. Ontogeny demonstrated enzyme-specific maturation patterns: CYP3A4 and CYP2C19 activity increased rapidly during infancy, whereas CYP2D6 and CYP1A2 matured more gradually, contributing to reduced neonatal clearance and prolonged half-life of several substrates. Clinically significant genotype–drug interactions were consistently reported for CYP2D6–codeine and CYP2C19–voriconazole/proton pump inhibitors, where poor or ultrarapid metabolizer phenotypes markedly altered exposure and toxicity risk. Evidence supports genotype-guided dosing and therapeutic drug monitoring for selected high-risk drugs. Conclusions: Pediatric drug clearance is governed by enzyme-specific maturation and functional polymorphisms. Integrating developmental dosing principles with targeted pharmacogenetic strategies may improve therapeutic precision and reduce avoidable toxicity in children.